2005
DOI: 10.1016/j.epsl.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally resolved stable isotope chronologies from northern Thailand deciduous trees

Abstract: Despite the existence of a number of climate proxies, the terrestrial expression of tropical climate variability over the past few centuries remains poorly resolved. We explore the applicability of stable isotope dendroclimatology as a tool for chronology and paleo-hydrology reconstruction on deciduous trees from monsoonal northern Thailand. Analysis of 11 trees coming from 4 different regions of northern Thailand yielded 7 records with varying degrees of δ 18 O and δ 13 C seasonality. We develop age models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 32 publications
9
74
1
Order By: Relevance
“…The relative humidity is ~90 % during the rainy season (generally, December-May) and drops by only 5-10 % during the moderate dry season (which lasts for about 3 months, around August). The reduction in relative humidity causes a reduction in the stomatal conductance of trees (Mooney et al 1983;Roberts et al 1990), increasing the δ 18 O of leaf water (Barbour 2007 and in seasonally dry forests in Thailand and Indonesia (Poussart et al 2004;Poussart and Schrag 2005). A similar relationship was also reported for a fast-growing species (Tachigali myrmecophila) in Amazonian terra firme forest near Manaus (Ballantyne et al 2011).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The relative humidity is ~90 % during the rainy season (generally, December-May) and drops by only 5-10 % during the moderate dry season (which lasts for about 3 months, around August). The reduction in relative humidity causes a reduction in the stomatal conductance of trees (Mooney et al 1983;Roberts et al 1990), increasing the δ 18 O of leaf water (Barbour 2007 and in seasonally dry forests in Thailand and Indonesia (Poussart et al 2004;Poussart and Schrag 2005). A similar relationship was also reported for a fast-growing species (Tachigali myrmecophila) in Amazonian terra firme forest near Manaus (Ballantyne et al 2011).…”
supporting
confidence: 52%
“…In addition, some ring boundaries seemed to have formed at the beginning of the moderate dry season, because many boundaries appeared with the sharp increase in δ 18 O wc variations. Similarly, the δ 18 O wc analysis suggested that the ring boundary formed at the end of the peak of the wet season for one species of deciduous dipterocarp tree in Thailand (Poussart et al 2005). Even in our limited study of three species, it was unclear how ring boundary formation was associated with the stable isotopic ring patterns.…”
Section: Efficacy Of Each Annual-ring Indicatormentioning
confidence: 92%
See 1 more Smart Citation
“…Such seasonal cycles of precipitation δ 18 O and relative humidity may generate seasonal cycles of tree ring cellulose δ 18 O, which can be used to identify annual growth (Anchukaitis et al, 2008;Anchukaitis and Evans, 2010;Evans and Schrag, 2004;Poussart and Schrag, 2005). To date, however, no such study has been performed in northern Southeast Asia.…”
mentioning
confidence: 99%
“…In addition, the application of bomb 14 C in various other research disciplines has grown significantly in the last 2 decades. In particular, atmospheric bomb 14 C has been used in forensic studies (Wild et al 1998;Zoppi et al 2004;Nakamura et al 2007;Buchholz and Spalding 2010;Alkass et al 2011;Ubelaker and Parra 2011;Ehleringer et al 2012), in biomedical research (Spalding et al 2005(Spalding et al , 2008Bhardwaj et al 2006;Lynnerup et al 2008), and in soil carbon studies (Quideau et al 2000;Bruun et al 2005;Koarashi et al 2009;Trumbore 2009;Rabbi et al 2013), to build reliable chronologies for recent terrestrial archives and materials (Hua 2009;English et al 2010;Hodge et al 2011;Clarke et al 2012;Hua et al 2012a), to validate tree-ring ages (Fichtler et al 2003;Vieira et al 2005;Bowman et al 2011;Pearson et al 2011), to date recent trees having no annual growth rings (Worbes and Junk 1989;Poussart and Schrag 2005;Lovelock et al 2010), and to determine biogenic and fossil fractions of industrial CO 2 emissions (Mohn et al 2008(Mohn et al , 2012Felner and Rechberger 2009;Palstra and Meijer 2010). This paper presents a new compilation of tropospheric 14 CO 2 (or tropospheric 14 C in short) for the last 60 yr , covering a short interval before the onset of bomb 14 C in the mid-1950s, the bomb-peak period during the 1960s, and the post-bomb era up to very recent time.…”
Section: Introductionmentioning
confidence: 99%